Early-church praxis: Selling land and possessions – A socio-historical study of Acts 2:45, 4:32–37 - Hombana, Mphumezi (HTS teologiese studies, 2023)
This article attempts to rethink the early church praxis of selling the land and possessions in response to some of the problems the 1st century church were confronted with. Hence, this article attempts to answer the questions: what were the social, economic, and religious factors that led to the selling of land and possessions in the early church, and what were the implications of this practice for the community, including issues related to exploitation, inequality, and long-term sustainability of resources? This article argues that the church in South Africa must lead the conversation and learn from the early church good example to respond to social ills of our time. This is without undermining the complexities that are part of this programme of action. This article is committed to socio-historical reading of the texts under inquiry as the means to respond to the questions raised in this study.Contribution: This article seeks to contribute to the ongoing debate on issues of land, possessions, and poverty in a South African context. It attempts to explore possible implications on issues that concern this article for churches in South Africa.